Analisis Kelayakan Usaha Perikanan Tangkap di Waduk Jatigede Kabupaten Sumedang - Ilva Viola; Atikah Nurhayati; Junianto (Jurnal Serambi Engineering, 2025)
This study aims to analyze the feasibility of capture fisheries in Jatigede Reservoir, Sumedang Regency, West Java. The research employed an accidental sampling method involving 32 active fishers, with primary data collected through interviews and questionnaires, and secondary data obtained from relevant agencies and literature review. The business feasibility analysis was conducted using income analysis, Break Even Point (BEP), Benefit Cost Ratio (BCR), and Payback Period (PP) methods. The results indicate that all fishing gear analyzed—gillnets, cast nets (kecrik), and fish traps (bubu)—met the feasibility criteria, as evidenced by BCR values greater than 1 and PP less than 3 years. The fish trap (bubu) demonstrated the best financial performance, with a BCR of 2.16 and a PP of 0.86 years. Therefore, capture fisheries in Jatigede Reservoir have strong potential to enhance the economic welfare of the local community.